Application of whole-brain CBV-weighted fMRI to a cognitive stimulation paradigm: Robust activation detection in a stroop task experiment using 3D GRASE VASO - Poser, Benedikt A.; Norris, David G. (Human brain mapping, 2011)
Brain activation studies generally utilize blood oxygenation level dependent (BOLD) contrast, most commonly measured using the gradient‐echo echo‐planar imaging (EPI) technique. BOLD contrast arises from regional changes in cerebral blood flow (CBF), cerebral blood volume (CBV), and the local metabolic rate of oxygen consumption. An alternative to BOLD is the detection of activation through direct measurement of these parameters. A noninvasive approach to measure activation‐related CBV changes is the vascular space occupancy (VASO) method, which exploits blood as an endogenous contrast agent by selectively nulling the magnetization of the water spins in the blood. Using a recently developed multislice variant of VASO that enables single‐shot whole‐brain coverage by virtue of a three‐dimensional GRASE readout, we here present the first application of VASO to an fMRI study with a whole‐brain cognitive task. Within acceptable measurement times (∼12 minutes), brain activation during a Stroop color‐word matching task could be detected reliably both on the group (N = 12) and single subject level, as evident from a qualitative comparison with separately acquired BOLD data and literature reports. Hum Brain Mapp, 2011. © 2010 Wiley‐Liss, Inc.